218k views
2 votes
Rewrite the function by completing the square.

h(x)=2x2+11x+15h(x)= 2 x^{2} +11 x +15


h(x)=2x


2


+11x+15

User Necreaux
by
5.8k points

1 Answer

7 votes

Answer:

h(x) = 2(x +11/4)^2 -1/8

Explanation:

h(x) = 2(x^2 +(11/2)x) +15

Add the square of half the x-coefficient inside parentheses. Subtract the same amount outside parentheses:

h(x) = 2(x^2 +(11/2)x +(11/4)^2) +15 -2(11/4)^2

h(x) = 2(x +11/4)^2 -1/8

Rewrite the function by completing the square. h(x)=2x2+11x+15h(x)= 2 x^{2} +11 x-example-1
User Brandon Yang
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.